Modeling of Transmitter and Receiver Layers in Hybrid Fiber Optic and Free Space Optical Communication - Ozdemir, M. Emin; Unverdi, N. Ozlem (IEEE, 2024)
The effects of the optical transmitter and receiver layers of hybrid optical communication systems with fiber and free-space optical (FSO) communication channels on data transmission performance were analyzed. The performance of hybrid optical communication systems with continuous wave laser (CW laser) or white light sources as well as NRZ (non-return to zero) or RZ (return to zero) pulse generators in optical transmitters was investigated. The effect of MZ (Mach-Zehnder) and EA (electroabsorption) modulators in optical transmitters on system performance was evaluated. In optical receivers, the performances of APD (Avalanche Photo Diode) and PIN (PIN Photo Diode), as well as Bessel, Gaussian, Butterworth, and Chebyshev optical filters, were examined. The quality factors, eye diagrams, and BER (bit error rate) of various hybrid communication systems designed with the OptiSystem 20.0 simulation software were examined and compared.
Keywords: Communication technologies; fiber optic communication; free space optical communications; optical transmitter; optical receiver; Computer Science; Engineering; Telecommunications